Circuit of Culture: Advocating Suicide Prevention and Eradication of Mental Illness Associated Stigma through ‘Into The Light Indonesia’ Campaign - Daina Pratiwi; Abhirama SD Perdana (President University, 2019)
Into the Light Indonesia is one of the most known communities that concerns about suicide intervention and the eradication stigma associated with mental illness in Indonesia. This research was analysing how Into the Light Indonesia is circulated and consumed by Indonesian through various media platforms especially social media. Circuit of culture is applied in this research in order to dig the understanding of how the meaning produced in this campaign is circulated and consumed by its audiences. There are still many people who are still not aware regarding this issues. The development of technology makes people easily receive and finding information in simple touch on their hands. Into the Light Indonesia brought this issues and successfully gained attention from its audiences by reaching 6,000 likes, 3,000 followers, published articles and invited to national and international talk shows. Into the Light Indonesia builds relationship with other communities that have the similar concerns relating to mental health. This research is applying cultural approach as the method to analyse based on each moment in the circuit of culture. This research will contribute to the literature journal of international public relation and practical significance in the related field.